Exergy Analysis and Optimization of Kamojang Geothermal Power Plant Dry Steam Type Capacity 55 MW - Rayhan Suryo Kusumo; Damora Rhakasywi; Fahrudin Fahrudin (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the exergy efficiency and irreversibility of the Kamojang Unit 2 Geothermal Power Plant (GPP) in Indonesia using an exergy analysis method. The results reveal that the turbine exhibits the highest exergy loss of 11,512 kW with an exergy efficiency of 82.78%. The condenser records the second-largest exergy loss of 9,875 kW, while the inter condenser and after condenser show the lowest exergy efficiencies at 22.6% and 38.55%, respectively. The overall system exergy efficiency is 65.3%, producing 63,261 kW of electricity from an input exergy of 96,764 kW. Optimization was conducted by varying the turbine inlet pressure from 4.5 to 6.5 bar, with the optimal pressure determined to be 4.5 bar, resulting in the highest exergy efficiency and the lowest irreversibility. This research provides valuable insights for enhancing geothermal power plant efficiency through thermodynamic parameter optimization.